Behavior Increase Body Immunity - Sri Mayasari Puspa (Fakultas Kesehatan Masyarakat Universitas Muhammadiyah Jakarta, 2021)
Covid-19 has spread to several countries including Indonesia. Responding to the growing trend of spreading and contagion of Covid-19, which has continued to increase, since April 2020. The Covid-19 pandemic has become a disruption so we need to recognize, overcome, and prevent this uncertainty so that this uncertainty will end soon To provide advice to all levels of society to be alert to the Covid-19 outbreak as an effort to reduce the spread of the Covid-19 outbreak, one of which is to increase body immunity. The method used in this study is a survey method used to analyze the role of employees of Cibinong Sentra Medika Hospital in increasing body immunity. The survey results showed that the average